Evaluation of a community-based performance arts programme for people who have experienced stroke in the UK: protocol for the SHAPER-Stroke Odysseys study. Issue 3 (11th March 2022) - Estevao, Carolina; Baldellou Lopez, Maria; Davis, Rachel E; Jarret, Lucinda; Soukup, Tayana; Bakolis, Ioannis; Healey, Andy; Harrington, Jean; Woods, Anthony; Crane, Nikki; Jones, Fiona; Pariante, Carmine; et al.
Abstract : Introduction: Stroke survivors, once in the community, face challenges with their long-term rehabilitation care and present higher levels of loneliness, depression and anxiety than the rest of the population. A community-based performance arts programme, Stroke Odysseys (SO), has been devised to tackle the challenges of living with stroke in the UK. In this study, we aim to evaluate the implementation, impact and experiences of SO for stroke survivors. Methods and analysis: Scaling-up Health Arts Programmes: Implementation and Effectiveness Research (SHAPER)-SO aims to scale-up SO to 75 participants and 47 stakeholders, while simultaneously evaluating the effectiveness and implementation of the programme. The main research aim is to evaluate the implementation, effectiveness, impact and experiences of a community-based performance arts programme (SO for stroke survivors). This mixed-methods study will evaluate the experience and impact of SO on those participating using mixed methods (interviews, observations and surveys) before and after each stage and carry out non-participant observations during a percentage of the workshops, training and tour. Data will be analysed using quantitative and qualitative approaches. This is a study within the SHAPER programme. Ethics and dissemination: Ethical approval has been granted by the King's College London PNM Research Ethics Panel, REC reference: LRS/DP-20/21–21549. Written informed consent will be sought for participants and stakeholders. The results of the study will be reported and disseminated at international conferences and in peer-reviewed scientific journals. Trial registration number: NCT04864470 .